Body size and social status in medieval Alba (Cuneo), Italy. Issue 3 (4th February 2019) - Weiss, Nicole M.; Vercellotti, Giuseppe; Boano, Rosa; Girotti, Marilena; Stout, Sam D.
Abstract: Objectives: Previous work by Vercellotti et al. in 2011 found significant status‐related differences in body size in males but not in females from the Italian bioarchaeological assemblage of San Michele di Trino (8th–14th centuries CE). The purpose of the present work is twofold: (a) to determine if status‐related body size differences could be observed in the nearby collection of San Lorenzo di Alba (7th–15th centuries CE) and (b) to add to the emerging narrative of medieval Italians. Materials and Methods: Osteometric data (maximum length for the humerus, radius, ulna, femur, tibia, and fibula; bicondylar length of the femur, condylo‐malleolar length of the tibia, foot height, maximum vertebral heights, and basion‐bregma height) were collected for 50 (20 female, 30 male) individuals from Alba, and Monte Carlo analysis was used to assess differences in skeletal element size, skeletal height, living stature, and body mass across sex and status. Results: Significant differences were detected between high status and low status males in Alba for radial maximum length ( p = 0.013), tibial maximum length ( p = 0.011), tibial condylo‐malleolar length ( p = 0.012), skeletal height estimated from condylo‐malleolar tibial length ( p = 0.002), and stature estimated from condyle‐malleolar tibial length with the age component ( p = 0.003). In contrast, no significant status‐based differences were observed between female subsamples ( p > 0.05). Discussion: The patterns of intrapopulation variation observed at Alba are similar but not as pronounced as those observed at Trino, suggesting that overall life conditions experienced by the two groups were comparable.